Interval Predictors for a Class of Uncertain Discrete-Time Systems - Meslem, Nacim; Martinez, John (Acta Cybernetica, 2020)
This work presents set-valued algorithms to compute tight interval predictions of the state trajectories for a certain class of uncertain dynamical systems. Based on interval analysis and the analytic expression of the state response of discrete-time linear systems, non-conservative numerical schemes are proposed. Moreover, under some stability conditions, the convergence of the width of the predicted state enclosures is proved. The performance of the proposed set-valued algorithms are illustrated through two numerical examples and the results are compared to that obtained with an other method selected from the literature.